Psychiatric morbidities and socio-demographic profile of patients attending psychiatric OPD in far western region of Nepal - Bhattarai, Nirajan; Adhikari, Ananta Prasad; Pandey, Araniko (Journal of Psychiatrists' Association of Nepal, 2024)
Introduction: Majority of the studies are conducted in urban communities of Nepal and there is a paucity of information about the psychiatric cases in rural communities. The present work was undertaken to study the psychiatric morbidities and socio-demographic profile of patients presenting at Psychiatric OPD in three different district hospitals of Far western region of Nepal. Methodology: A quantitative descriptive cross-sectional study was conducted in three hospitals namely Baitadi District Hospital, Bajhang District Hospital and Dadeldhura District Hospital of the far western region of Nepal. All new patients reporting to psychiatric OPD from April 2020-May 2023 A.D formed the study population and the follow up cases were excluded from the study. ICD 10 (DCR) was used for diagnosis and verified by two consultant psychiatrists and analyzed using SPSS version 20. Results: Out of total 932 respondents enrolled in this study, slight preponderance of male (52.3%) was observed. Majority of the respondents (67.4%) were married. Anxiety disorders (27.6%) emerged as largest group followed by depression (14.6%). Other commonly diagnosed cases were psychotic disorders (11.8%), somatoform disorders (10.6%), primary headache (8.8%), alcohol dependence syndrome (6.4%) and epilepsy (4.7%). Majority of the respondents were from Dadeldhura (52.1%) followed by Bajhang (24.3%). 14.6% of the respondents had family history of mental disorders, and 14.8% had one or more comorbidities. Conclusion: The study concludes that there is high proportion of psychiatric morbidities in rural hospitals of Nepal. This also calls the need to strengthen the mental health services in the rural community and to address the psychiatric cases.